2013
DOI: 10.1590/s0004-282x2013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring respiratory muscle strength assists in early diagnosis of respiratory dysfunction as opposed to the isolated use of pulmonary function evaluation in amyotrophic lateral sclerosis

Abstract: In ALS, monitoring respiratory muscle strength assists in early diagnosis of respiratory dysfunction as opposed to the isolated use of FVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
6
2
Order By: Relevance
“…Notwithstanding, respiratory muscle strength tests and pulmonary function assessments are not routinely used (19). In a 2009 survey of consultant neurologists in the United Kingdom investigating NIV use in patients with ALS, only 38% of respondents reported assessing respiratory function initially and only 20% routinely monitored it (20).…”
Section: Measuring Respiratory Function In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, respiratory muscle strength tests and pulmonary function assessments are not routinely used (19). In a 2009 survey of consultant neurologists in the United Kingdom investigating NIV use in patients with ALS, only 38% of respondents reported assessing respiratory function initially and only 20% routinely monitored it (20).…”
Section: Measuring Respiratory Function In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…However, studies examining the relationships between VC and other respiratory measures have yielded variable results likely related to different methodologies used in the different studies. For example, when pulmonary function (FVC) and respiratory muscle strength (MIP, MEP, and SNIP) were assessed in ALS patients and matched healthy subjects, a positive correlation was recorded between FVC/SNIP, FVC/MIP, and FVC/MEP in ALS patients (19). However, a prospective, randomized study of 20 ALS patients found no correlation between FVC and MIP, MEP, or peak cough expiratory flows (38).…”
Section: Cross Correlations Of Respiratory Measuresmentioning
confidence: 99%
“…Furthermore, all cohorts used FVC to measure respiratory function, except the cohort in Dublin (Ireland), which used sniff nasal inspiratory pressure (SNIP), which is known to be correlated with FVC. 25 Based on patients in the Dublin cohort for whom we had information about both FVC and SNIP, we transformed SNIP data of all patients to FVC to allow comparability between cohorts.…”
Section: Methodsmentioning
confidence: 99%
“…Respiratory failure caused by muscle weakness is one of the most common causes of death in neuromuscular disorders, and measurement of respiratory muscle strength is of prognostic value. Thus far, however, no single test of respiratory function can reliably predict the presence of hypercapnia . Spirometry, which includes assessment of forced vital capacity (FVC), is the most common test recommended for monitoring respiratory dysfunction.…”
mentioning
confidence: 99%
“…Thus far, however, no single test of respiratory function can reliably predict the presence of hypercapnia. 2,3 Spirometry, which includes assessment of forced vital capacity (FVC), is the most common test recommended for monitoring respiratory dysfunction. However, the test outcome depends on patient effort, and the test may be difficult to conduct in patients with dementia, faciobulbar weakness, or reduced motivation.…”
mentioning
confidence: 99%